Adventitious rooting in microshoots of chestnut hybrid (Castanea sativa x C. crenata) in the presence of indole-3-butyric acid: The role of changes in endogenous indole-3-acetic acid, indole-3-acetylaspartic acid and indole-3- butyric acid levels - Gonçalves, J.C. (2011)
Endogenous levels of IAA, IAAsp and IBA were quantified during the first 8 days of in vitro rooting of the chestnut hybrid, clone M3 by high performance liquid chromatography. Rooting was induced either by dipping the basal ends of the shoots into 1 gl-1 IBA solution for 1 minute or by subculturing the shoots on agar rooting medium with 3 mgl-1 IBA for 5 days. For root development the induced shoots were transferred to auxin-free agar medium. Auxins were measured in the apical and basal parts of the shoots by means of high performance liquid chromatography. Endogenous levels of IAA and IAAsp were higher in IBA-treated shoots than in control shoots. In extracts of the basal parts of the shoots, the concentration of free IAA showed a transient peak at day 2, in both root inductive methods, a subsequent gradual decrease for the remainder of the time course was observed. The concentration of IAAsp peaked at day 6 in extracts of the basal parts of shoots induced with 3 mgl-1 IBA for 5 days, whereas shoots induced by dipping showed an initial increase until day 2, and then remained stable. In extracts from basal shoot portions induced by dipping and by IBA in the medium, IBA concentration showed a transient peak at 24 h and 48 h, respectively, remaining stable after day 4 for the dipping method, whilst showing a significant drop between day 4 and 6 for the other induction treatment. All quantified auxins remained at a relatively low level, virtually constant, in extracts from apical shoot portions, as well as in extracts from control of non-rooting shoots.